MAC para a comunidade - Gonçalves, Lisbeth Rebollo; Silva, Dilma de Melo (Comunicação & Educação, 1995)
List of the research, teaching and university extension activities of the Education Division of USP's Museu de Arte Contemporânea (Museum of Contemporary Art).